Personality matters – The interplay between consistent individual differences and mouse welfare in female C57BL6/J mice - Sroka, Marlene G. U.; Ambree, Oliver; Dohmen, Celina; Palme, Rupert; Kaiser, Sylvia; Richter, S. Helene (Frontiers in Animal Science, 2024)
To ensure good welfare of animals in human hands, it is essential to modify housing conditions according to the animals’ needs. Traditionally, the effects of such modifications are studied by means of group-level comparisons, thereby widely neglecting consistent inter-individual differences (i.e., so-called ‘animal personalities’). However, as animals with distinct personality types might differ in their environmental needs and hence react differently to the same environment, such systematic inter-individual differences might have important welfare consequences. This becomes particularly apparent under laboratory conditions, where animals are typically housed under highly standardized and barren environments. Against this background, we here aim to investigate personality-dependent welfare consequences in response to different housing conditions in laboratory mice. Female C57BL/6J mice were characterized for their personality type in exploration behavior and the most and the least explorative individuals were set up in either simple or in highly complex housing conditions that included constantly changing environmental enrichment items. We monitored individual welfare by studying behavioral, physiological, and immunological outcome measures. Besides personality-dependent differences in immune parameters and overall improved welfare under complex housing conditions, we indeed found hints that individual mice were differently affected in their welfare depending on the specific combination of personality type and housing condition. Specifically, highly explorative mice appeared to be more adversely affected by simple housing, but also profited more from complex housing compared to low explorative mice. These findings indicate that welfare promoting adjustments do not necessarily benefit all individuals equally and therefore, call for a shift of perspectives in the evaluation of animal welfare.